Inactivation of Salmonella enterica and Surrogate Enterococcus faecium on Whole Black Peppercorns and Cumin Seeds Using Vacuum Steam Pasteurization - Newkirk, Jordan J.; Wu, Jian; Acuff, Jennifer C.; Caver, Chris B.; Mallikarjunan, Kumar; Wiersema, Brian D.; Williams, Robert C.; Ponder, Monica A. (Frontiers in Sustainable Food Systems, 2018)
Spices, including black pepper and cumin seeds, have been implicated in outbreaks of salmonellosis and prompted recalls of ready-to-eat products containing contaminated spices. Vacuum-assisted steam pasteurization is performed to improve the safety and quality of many low water activity products, however process parameters associated with inactivation on whole spices are not well described. The objective of this study was to determine the effectiveness of a lab-scale vacuum-assisted steam process for the inactivation of Salmonella enterica and its potential surrogate Enterococcus faecium ATCC 8459 inoculated onto the surface of whole peppercorns and cumin seeds. In addition, the effect of two inoculation preparation methods [growth on tryptic soy agar (TSA) or inclusion within a native microbiota biofilm], on the reduction of S. enterica serovars or E. faecium was compared on steam pasteurized whole black peppercorns. Spices were processed using steam under a vacuum to achieve a mean product temperature of 86.7 ± 2.8°C for different dwell times. Salmonella inoculated using the TSA-grown method, required 83 and 70 s respectively to achieve a 5-log reduction of Salmonella on peppercorns and cumin seeds. Longer time periods were needed to achieve a 5-log reduction of Salmonella when it was present in a native biofilm on whole peppercorns. Survivor estimations were best predicted by the Weibull models. The mean log reductions of E. faecium were 0.9 log CFU/g lower than Salmonella on whole black peppercorns inoculated using the TSA-grown cells (P = 0.0021). The mean log reductions of Salmonella and E. faecium prepared using the biofilm-inclusion method were not significantly different (P = 0.76). E. faecium log CFU/g reductions were not significantly different compared to Salmonella on whole cumin seeds (P = 0.42) indicating that while reductions are comparable the surrogate may not always provide a conservative indication of complete Salmonella elimination for all spices processed using vacuum-assisted steam. Highlights - E. faecium is a surrogate for Salmonella on steam processed whole black peppercorn. - E. faecium is not a conservative surrogate for Salmonella on steam processed >85°C whole cumin.